Designed, synthesized and biological evaluation of proteolysis targeting chimeras (PROTACs) as AR degraders for prostate cancer treatment. (1st September 2021) - Liang, Jian-Jia; Xie, Hang; Yang, Rui-Hua; Wang, Ni; Zheng, Zi-Jun; Zhou, Chen; Wang, Ya-Lei; Wang, Zhi-Jia; Liu, Hong-Min; Shan, Li-Hong; Ke, Yu
Graphical abstract: Two series of proteolysis targeting chimeras (PROTACs) containing the phthalimide degrons with different linker were identified. Compound A16 displayed the most potent inhibition against LNCaP and showed excellent AR degradation efficacy at 30 μM. Highlights: Two series of novel PROTACs and androgen receptor degradation efficacy have been discovered. The best compound A16 displayed excellent binding affinity and AR degradation activity. Molecular docking analysis illustrates the possible dual mechanism actions of these compounds with AR and E3 ligase. Abstract: As a continuation of our research on developing potent and potentially safe androgen receptor (AR) degrader, a series of novel proteolysis targeting chimeras (PROTACs) containing the phthalimide degrons with different linker were designed, synthesized and evaluated for their AR degradation activity against LNCaP (AR+) cell line. Most of the synthesized compounds displayed moderate to satisfactory AR binding affinity and might lead to antagonist activity against AR. Among them, compound A16 exhibited the best AR binding affinity (85%) and degradation activity against AR. Due to the strong fluorescence properties of pomalidomide derivatives, B10 was found to be effectively internalized and visualized in LNCaP (AR + ) cells than PC-3 (AR-) cells. Moreover, the molecular docking of A16 with AR and the active site of DDB1-CRBN E3 ubiquitin ligase complex provides guidance to design new PROTAC degrons targeting AR for prostate cancer therapy. These results represent a step toward the development of novel and improved AR PROTACs.